Prolonged Sitting Posture: Massage and Physical Exercise Program as Effective Therapy in 45 Sedentary Officers using Their Vehicles Full Time - DOSSOU, Sémako Gérard; LAWANI, MOHAMED MANSOUROU; YESSOUFOU, Lafiou; Tigri, Tertulie Nawal; HOUETO, Vignon Gratien; Lawani, Mohamed Nadil Olabiss (My University, 2021)
The high prevalence of low back pain associated with prolonged sitting as a result of work demands, is a major public health problem. Added to this is the sedentary lifestyle and full-time use of vehicles, keeping workers in this seated position. We now know the many benefits of regular exercise and physical activity. Inactivity is considered a risk factor associated with the development of lower back pain. We undertook this study to make subjects aware of the consequences of this posture. In addition, we wanted to help them relieve lower back pain and functional disability caused by prolonged sitting posture. To achieve this, we have set ourselves the goal of assessing the effect that the combination of a physical exercise program and massage with shea butter could have on lumbar pain and functional disability in inactive sedentary officials with full-time lumbar pain driving their vehicles. To achieve this goal, we brought together 45 subjects divided into three experimental groups. The results show that the group receiving the combination of an exercise and massage program with shea butter, experienced a significant decrease in pain and functional disability over the 6 weeks. Thus, the combination of an exercise and massage program with shea butter allows effective management of pain and functional disability in inactive sedentary officials.
Keywords: Exercise program; massage; shea butter; prolonged sitting posture; inactive sedentary; posture